The Influencing Factors of Computer Adoption in Agribusiness: A Preliminary Study - Sudaryanto, Sudaryanto (International Research Journal of Business Studies, 2011)
This research is aimed to investigate factors that influence the intentions of adopting computer for business purpose, and theirimplications on managerial development. Semi structured interview and courier mailed survey had been employed to collect the data. A conceptual framework and theoretical insight presented based on literature review and primary data collected from the various east java agribusiness. To develop qualitative information of sample characteristics, cross tabulation was employed. Logistic regression was used to test the research hypotheses. The research findings show that the intention to adopt computer in east java agribusiness is strongly influenced by managers whose ages are 41+, education (TAFE/D3), and sales volume. This research has a direct implication on agribusiness development for the overall east java agribusiness and provinces in Indonesia. It is expected that it will encourage other researchers to conducting similar research benchmarking with other developing countries. The complexity and wide range of agribusiness term made the research methodology complicated.